2003
DOI: 10.1111/j.1527-3466.2003.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

DX‐9065a, a Direct Inhibitor of Factor Xa

Abstract: The synthetic compound DX-9065a represents a low molecular weight, direct, competitive inhibitor of factor Xa (FXa) with a high affinity and selectivity for the enzyme. Under experimental conditions DX-9065a exerts strong anticoagulant actions in vitro and in vivo and is antithrombotically effective in various thrombosis models. It inhibits proliferation of vascular smooth muscle cells in cell culture systems as well as in in vivo models. As a small molecule inhibitor, DX-9065a inactivates both free and fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Several studies demonstrated that inhibition of Factor Xa reduces VSMC proliferation [31], and restenosis after balloon angioplasty [3135]. At the molecular level, wound healing and fibrosis share similar mechanisms, including fibroblast migration, proliferation and subsequent differentiation into myofibroblasts that typically express α -SM actin [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that inhibition of Factor Xa reduces VSMC proliferation [31], and restenosis after balloon angioplasty [3135]. At the molecular level, wound healing and fibrosis share similar mechanisms, including fibroblast migration, proliferation and subsequent differentiation into myofibroblasts that typically express α -SM actin [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of vascular remodeling during atherosclerosis, restenosis and intimal hyperplasia, FXa promotes smooth muscle cell proliferation and migration [31,[73][74][75][76] and (as indicated above) FXa induces the differentiation of fibroblasts into myofibroblasts [61]. These data support the hypothesis that FXa-dependent signal transduction plays an important role in tissue remodeling.…”
Section: Functional Consequences Of Fxa Signaling In Tissue Remodelinmentioning
confidence: 68%
“…These data support the hypothesis that FXa-dependent signal transduction plays an important role in tissue remodeling. In line with this hypothesis, FXa inhibition reduces vascular smooth muscle cell proliferation [74] and restenosis after balloon angioplasty [74,[77][78][79][80]. However, the inhibition of FXa also diminishes thrombin generation, which is well-known to be deleterious in vascular remodeling [81].…”
Section: Functional Consequences Of Fxa Signaling In Tissue Remodelinmentioning
confidence: 89%
“…DX-9065a is a reversible, highly selective competitor for factor Xa. It has been shown to be an effective anticoagulant whether applied subcutaneously, intravenously or orally [40], although the oral bioavailability of DX-9065a is too low for clinical usability [41]. First clinical trials in patients with coronary artery disease were positive and phase II trials initiated.…”
Section: Direct Factor Xa Inhibitorsmentioning
confidence: 99%